Aweak phenotype associated with novel ABO*A allele variant c.106delinsGG - Sanmukh Ratilal Joshi; Glenda Millard; Mayuri Vekariya; Priya Radadiya; Manisha Rajapara; Hiren Dhanani; Gaurav Shastri; Prabhat Sharma; Brett Wilson; Yew-Wah Liew (Asian Journal of Transfusion Science)
BACKGROUND AND OBJECTIVES: Discrepancy between forward and reverse ABO grouping could be due to several reasons including genetic mutations of the alleles encoding group specific transferase. The healthy donors found with weak A antigen were investigated to ascertain the allele responsible for variation. MATERIALS AND METHODS: Standard serological methods were employed using commercial antisera. The molecular sequencing was performed on DNA with enrichment library prep kit and a custom designed overlapping probe panel. Binary alignment mapping files, generated on board the Illumina MiSeq instrument and aligned to the GRCh37/Hg19 reference genome, were uploaded to the QIAGEN CLC genomics workbench software (version. 20) where variant call files were generated and analyzed. RESULTS: Red blood cells (RBCs) of six healthy donors, showing weak mix-field agglutination by anti-A and anti-A, B and plasma with absence or weakly reacting anti-A, were investigated serologically. The RBCs incubated with anti-A yield positive elution and their saliva lacked A but possessed H antigen thereby classifying as a historical known phenotype Aend. Family study on 4 probands showed inheritance of the trait. Molecular studies revealed presence of ABO*A allele carrying rare novel variant referred to as c.106delinsGG in line with HGVS recommendation that was thought to be responsible for the variant of A. CONCLUSION: Six cases serologically defined as Aweak were found to be associated with novel allele ABO*A (c.106delinsGG). The Aweak phenotype with the novel allele has not been displayed on International Society of Blood Transfusion database, though c.106delinsGG is listed in the UCSC genome browser under rs782544248.